Restrictive fluids versus standard care in adults with sepsis in the emergency department (REFACED): A multicenter, randomized feasibility trial. (5th August 2022) - Jessen, Marie K.; Andersen, Lars W.; Thomsen, Marie‐Louise H.; Kristensen, Peter; Hayeri, Wazhma; Hassel, Ranva E.; Messerschmidt, Tina G.; Sølling, Christoffer G.; Perner, Anders; Petersen, Jens Aage K.; Kirkegaard, Hans
Abstract: Background: Fluid treatment in sepsis is a challenge and clinical equipoise exists regarding intravenous (IV) volumes. We aimed to determine whether a 24‐h protocol restricting IV fluid was feasible in adult patients with sepsis without shock presenting to the emergency department (ED). Methods: The REFACED Sepsis trial is an investigator‐initiated, multicenter, randomized, open‐label, feasibility trial, assigning sepsis patients without shock to 24 h of restrictive, crystal IV fluid administration or standard care. In the IV fluid restriction group fluid boluses were only permitted if predefined criteria for hypoperfusion occurred. Standard care was at the discretion of the treating team. The primary outcome was total IV crystalloid fluid volumes at 24 h after randomization. Secondary outcomes included total fluid volumes, feasibility measures, and patient‐centered outcomes. Results: We included 123 patients (restrictive 61 patients and standard care 62 patients) in the primary analysis. A total of 32% (95% confidence interval [CI] 28%–37%) of eligible patients meeting all inclusion criteria and no exclusion criteria were included. At 24 h, the mean (±SD) IV crystalloid fluid volumes were 562 (±1076) ml versus 1370 (±1438) ml in the restrictive versus standard care group (mean difference –801 ml, 95% CI −1257 to −345 ml, p = 0.001). Protocol violations occurred in 21 (34%) patients in the fluid‐restrictive group. There were no differences between groups in adverse events, use of mechanical ventilation or vasopressors, acute kidney failure, length of stay, or mortality. Conclusions: A protocol restricting IV crystalloid fluids in ED patients with sepsis reduced 24‐h fluid volumes compared to standard care. A future trial powered toward patient‐centered outcomes appears feasible.